Rancang Bangun Mesin Pencuci Sekaligus Peniris Potongan Nanas Otomatis - hendriko, hendriko; Kajo, Teddy Pradipta; Jaenudin, Jajang; Khamdi, Nur; Tianur, Tianur (Jurnal Keteknikan Pertanian, 2021)
Indonesia is a country that produce a large variety and quantity of fruit. One of the prominent fruits is pineapple. Small and medium-sized industries that process pineapples into derivative products have sprung up in various regions. However, most of the processing is still conducted manually. One thing that still needs to be improved is the washing and drying process. Therefore, this research developed an automatic washing and drying machine. The developed machine uses a one-tube system so it could reduce the transfer process from one stage to the next. Testing on the developed machines has been carried out. The test results show that this machine is capable to process as much as 6.5 kg of pineapple in one batch. Another test to determine the most effective duration of washing and drying process was also carried out. The test results show that the effective washing time is 180 seconds, and the drying process is 90 seconds. Apart from the level of cleanliness and dryness of pineapple, this test also observes the damage of pineapple as a result of the washing and drying process. Simulations to measure the total time to operate the machine have been carried out. The data shows that it takes 303 seconds, starting from inserting pineapple to the tube, washing, draining, and finally removing pineapples from the tube. By using both data of average total processing time and optimum weight, the capacity of developed machine could be calculated. The capacity of this machine is around 77 kg per hour or 8.008 kg per month. With this capacity, this machine can be used by SME with a large production capacity.